2020
DOI: 10.1016/j.jval.2019.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting for Treatment Switching in Oncology Trials: A Systematic Review and Recommendations for Reporting

Abstract: Objectives: To systematically review the quality of reporting on the application of switching adjustment approaches in published oncology trials and industry submissions to the National Institute for Health and Care Excellence Although methods such as the rank preserving structural failure time model (RPSFTM) and inverse probability of censoring weights (IPCW) have been developed to address treatment switching, the approaches are not widely accepted within health technology assessment. This limited acceptance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Many of the included models adjusted for treatment switching, but none provided rationales for the adjustment methods selected. This lack of adequate justification for method choice is in line with the findings of an SLR of published trials and industry submissions in oncology [ 59 ], which claimed that the quality of reporting on implementation of a switching adjustment was generally poor. In agreement with the recommendations of Sullivan et al [ 59 ], future CEAs that employ treatment-switching adjustment should discuss whether the underlying assumptions corresponding to the chosen adjustment method are met in the specific application and should present a visual comparison of observed and adjusted OS curves.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Many of the included models adjusted for treatment switching, but none provided rationales for the adjustment methods selected. This lack of adequate justification for method choice is in line with the findings of an SLR of published trials and industry submissions in oncology [ 59 ], which claimed that the quality of reporting on implementation of a switching adjustment was generally poor. In agreement with the recommendations of Sullivan et al [ 59 ], future CEAs that employ treatment-switching adjustment should discuss whether the underlying assumptions corresponding to the chosen adjustment method are met in the specific application and should present a visual comparison of observed and adjusted OS curves.…”
Section: Discussionmentioning
confidence: 70%
“…This lack of adequate justification for method choice is in line with the findings of an SLR of published trials and industry submissions in oncology [ 59 ], which claimed that the quality of reporting on implementation of a switching adjustment was generally poor. In agreement with the recommendations of Sullivan et al [ 59 ], future CEAs that employ treatment-switching adjustment should discuss whether the underlying assumptions corresponding to the chosen adjustment method are met in the specific application and should present a visual comparison of observed and adjusted OS curves. A comparison of different switching adjustment methods and recommendations for their application is available in published literature [ 59 ] and in a NICE technical support document [ 60 ].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Treatment switching (‘switching’) in oncology trials is common [ 9 ]. For the PROfound trial it was agreed with the steering committee and regulatory bodies (FDA and EMA) that switching from control to olaparib should be allowed upon radiographic progression (blinded independent central review (BICR)-confirmed up to data cutoff (DCO)1 and investigator-assessed beyond DCO1) if appropriate for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation studies have shown that these methods tend to produce more accurate estimates of the switching-adjusted estimand than simple adjustment methods or a standard intention to treat (ITT) analysis. See Jimenez et al (2017), Latimer, K. R. Abrams, et al (2018), and Sullivan et al (2020) for a systematic review of their applications. However, their performance can be compromised when the key underlying assumption of “no unmeasured confounding” is violated.…”
Section: Introductionmentioning
confidence: 99%